Co-Development of AICCRA Ghana Cluster Partnerships on NFCS, One-Health, Ag-data hub and EWRR Cluster - Clottey, Victor; Yeboah, Stephen; Martey, Francisca; Dalaa, Mustapha Alasan; Tepa-Yotto, Ghislain; Yao, Osae Michael (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This paper highlights the draft partnership agreements developed by stakeholders in the agriculture sector of Ghana to became necessary to promote partnerships for the National Framework for Climate Services (NFCS), One-Health, Ag-data hub, and Early Warning & Rapid Response for pests and diseases (EWRR).